PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN SISWA TENTANG PUBERTAS DI SDN PASIRLUHUR KABUPATEN BANDUNG - Meliyanti, Mira; Aisah, Aisah; Syafrullah, Haidir; Rosita, Rosita (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
A lack of knowledge about puberty can lead to discomfort, emotional instability, and risky behaviors such as dating, casual sex, and early pregnancy. According to the World Health Organization (WHO), adolescents make up 18% of the global population. Puberty typical early occurring between the ages of 9 and 13. Report from the Indonesian Demographic and Health Survey (SDKI) shows that 13.3% of adolescent girls are unaware of the physical changes that occur during puberty. This study aims to examine the effect of health education delivered through animated video media on students’ knowledge about puberty at SDN Pasirluhur, Bandung Regency. The research uses a quantitative approach with a quasi-experimental design, specifically a pretest-posttest nonequivalent group design. The sample consists of 170 respondents, with 85 students in the animated video intervention group and 85 in the control group without intervention. Findings reveal that before the intervention, only 8.2% of students in the intervention group had good knowledge, which increased to 44.7% afterward. In contrast, in the control group, 84% of students initially had poor knowledge, and after the posttest without intervention, 80.0% still showed no improvement. An Independent T-test analysis produced a p-value of 0.000 at a 0.05 significance level, indicating a statistically significant difference. In conclusion, the study demonstrates that health education using animated video media significantly improves students’ knowledge about puberty.